Lack of PRKD2 and PRKD3 kinase domain somatic mutations in PRKD1 wild-type classic polymorphous low-grade adenocarcinomas of the salivary gland - Piscuoglio, Salvatore; Fusco, Nicola; Ng, Charlotte K Y; Martelotto, Luciano G; da Cruz Paula, Arnaud; Katabi, Nora; Rubin, Brian P; Skálová, Alena; Weinreb, Ilan; Weigelt, Britta; Reis-Filho, Jorge S (Histopathology, 2016)
AIMS: Polymorphous low-grade adenocarcinoma (PLGA) is the second most common intra-oral salivary gland malignancy. The vast majority of PLGAs harbour a PRKD1 E710D hot-spot somatic mutation or somatic rearrangements of PRKD1, PRKD2 or PRKD3. Given the kinase domain homology among PRKD1, PRKD2 and PRKD3, we sought to define whether PLGAs lacking PRKD1 somatic mutations or PRKD gene family rearrangements would be driven by somatic mutations affecting the kinase domains of PRKD2 or PRKD3. METHODS AND RESULTS: DNA was extracted from eight microdissected PLGAs lacking PRKD1 somatic mutations or PRKD gene family rearrangements. Samples were thoroughly centrally reviewed, microdissected and subjected to Sanger sequencing of the kinase domains of the PRKD2 and PRKD3 genes. None of the PLGAs lacking PRKD1 somatic mutations or PRKD gene family rearrangements harboured somatic mutations in the kinase domains of the PRKD2 or PRKD3 genes. CONCLUSION: PLGAs lacking PRKD1 somatic mutations or PRKD gene family rearrangements are unlikely to harbour somatic mutations in the kinase domains of PRKD2 or PRKD3. Further studies are warranted to define the driver genetic events in this subgroup of PLGAs.
Keywords: sekvenční seřazení; Adenocarcinoma; Humans; Sanger sequencing; salivary gland tumours; mikrodisekce; lidé středního věku; Sequence Analysis, DNA; sequence homology; kinase domain; Female; mutace; Aged; dospělí; Microdissection; Salivary Gland Neoplasms; Salivary Glands; senioři; lidé; proteinové domény; Genotype; nádory slinných žláz; sekvenční analýza DNA; Adult; Amino Acid Sequence; ženské pohlaví; Male; Middle Aged; mutation; slinné žlázy; Sequence Alignment; Protein Domains; Protein Kinase C; Gene Rearrangement; genotyp; adenokarcinom; genová přestavba; proteinkinasa C; Mutation; mužské pohlaví; sekvence aminokyselin